A SURVEY OF DATA QUALITY IN INDUSTRIAL NETWORKS AND ENHANCING THEIR RELIABILITY COMPLEX INDICATOR FOR THE NEEDS OF THE INDUSTRY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
With the evolution of the industrial sector, the establishment and administration of production units have emerged as primary concerns for each industrial enterprise. For the control process, emphasis is placed on programmable devices and industrial networks. Through them, manufacturing enterprises face two main questions, "What reliability could they provide?" and "Is it possible to improve the current devices they use." In this article, an experimental study related to the information level of an industrial network is carried out. It aims to increase the quality and speed of her workflow. Monitoring and data extraction of the communication of programmable devices is carried out as well. A method for improving data transmission in the same network is proposed. A statistical method is used to analyze the general reliability. Also the present article aims to develop a computational model of a complex indicator of the reliability of a system of programmable devices. The choice is based on the fact that many enterprises rely on the rapid processing of information and greater reliability of programmable devices.